2022
DOI: 10.1002/acr.24523
|View full text |Cite
|
Sign up to set email alerts
|

One‐Year Treatment Outcomes of Secukinumab Versus Tumor Necrosis Factor Inhibitors in Spondyloarthritis: Results From Five Nordic Biologic Registries Including More Than 10,000 Treatment Courses

Abstract: Register of Biological Treatment (ROB-FIN), and Norwegian Antirheumatic Drug Register (NOR-DMARD) registriesObjective. To describe baseline characteristics and to compare treatment effectiveness of secukinumab versus tumor necrosis factor inhibitors (TNFi) in patients with spondyloarthritis (SpA) using adalimumab as the main comparator.Methods. This was an observational, prospective cohort study. Patients with SpA (clinical ankylosing spondylitis, nonradiographic axial SpA, or undifferentiated SpA) starting se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…1 Randomised controlled trials (RCTs) of treatment of axSpA typically focus on axial disease activity, [2][3][4] where the effect appears to be similar across the different tumour necrosis factor inhibitors (TNFi). 5 For secukinumab and ixekizumab, indirect comparison of the results from their pivotal RCTs, together with a large observational study, 6 suggest that the effect of interleukin 17-inhibitors (IL-17i) on axial disease is in line with that of TNFi. 2 3 7 Whereas the effects on axial disease may be similar, the effects on other SpA manifestations seem to vary substantially.…”
Section: Introductionmentioning
confidence: 99%
“…1 Randomised controlled trials (RCTs) of treatment of axSpA typically focus on axial disease activity, [2][3][4] where the effect appears to be similar across the different tumour necrosis factor inhibitors (TNFi). 5 For secukinumab and ixekizumab, indirect comparison of the results from their pivotal RCTs, together with a large observational study, 6 suggest that the effect of interleukin 17-inhibitors (IL-17i) on axial disease is in line with that of TNFi. 2 3 7 Whereas the effects on axial disease may be similar, the effects on other SpA manifestations seem to vary substantially.…”
Section: Introductionmentioning
confidence: 99%
“…Secukinumab, an interleukin (IL)-17A inhibitor, has demonstrated sustained improvement in the signs and symptoms of active AS in the MEASURE clinical trial program [5,6,12,14,15]. The impact of sex on the efficacy of secukinumab has not been thoroughly evaluated and although comparative effectiveness in the real-world setting between TNFi and secukinumab has been previously reported, stratification by sex was not investigated further [16,17]. In this post hoc analysis, we report efficacy and safety data pooled from five phase 3 MEASURE studies with respect to sex in patients with active AS treated with secukinumab through 52 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…6 ) [ 58 , 59 , 63 , 64 ]. Retention was highest when secukinumab was used as the first biological agent (76–84% at 12 months), but decreased with subsequent lines of treatment (67–75% as second-line biological and 56–66% as third-line) [ 58 , 65 , 66 ]. The most common reason for treatment discontinuation in these real-world studies was insufficient efficacy [ 58 , 59 , 63 , 66 ], and data from EuroSpA showed that this was also the most common reason for discontinuing TNF inhibitor therapy [ 58 ].…”
Section: Methodsmentioning
confidence: 99%